Digital art in Ireland : new media and Irish artistic practice - O'Sullivan, James; O'Sullivan, James (Anthem Irish studies, 2021)
This collection of essays explores digital art in Ireland. Comprising contributions from scholars and practitioners, it examines how new media technologies are shaping the island?s contemporary artistic practices. As one of the first dedicated treatments of Irish digital art, it fills a major gap in the national media archaeology of Ireland